Pendaftaran Peralihan Hak Milik Atas Tanah Berdasarkan Akta Jual Beli Yang Sudah Lewat Waktu di Kota Padang - Zaki, M.; Warman, Kurnia; Syofiarti, Syofiarti (Universitas Ekasakti, 2023)
PPAT has the responsibility to make a Deed of Sale and Purchase (AJB) as proof of the transfer of land rights and register it with the National Land Agency. However, BPN often does not meet the specified time limits, potentially harming land owners and creating potential legal disputes. This emphasizes the need to consider the legal implications of this delay to ensure the validity of land ownership rights and avoid future legal problems, especially with the rapid economic growth in Padang City. This research uses a juridical-empirical approach. Guidance and supervision have not been running optimally so that there are still PPATs who commit violations and appear to ignore the sanctions that have been given. For PPATs who commit violations or negligence, the Head of the Land Office will give sanctions in the form of written warnings and unwritten or verbal warnings as regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 2 of 2018 concerning the Development and Supervision of Officials Making Land Deeds. The obstacles in implementing PPAT guidance and supervision by Padang City Land Office officials are time and budget.